Kulturna in družbena angažiranost v kontekstu digitaliziranega vsakdana - Oblak Črnič, Tanja (Družboslovne razprave, 2018)
The articles explores the relationships between position of culture in everyday life of young people, their media consumption and civic engagement, by focusing on the role of digital media. Among others, the study shows the limitations of universal understanding of the youth. Based on the results of a quantitative online survey among 793 young people in Ljubljana, this study identifies distinctive types of youth cultural involvement: the biggest group is apolitical and from the cultural events excluded youth, while the socially and politically most engaged youth seem to be the so called "cultural creators".
Keywords: Culture; Digital media; Družbena aktivnost; Elektronski mediji; Everyday life; Kultura; Mladina; Political participation; Politična participacija; Social engagement; Vsakdanje življenje; Youth